2021
DOI: 10.1021/acsaem.0c03087
|View full text |Cite
|
Sign up to set email alerts
|

Cu–Pb Nanocomposite Cathode Material toward Room-Temperature Cycling for All-Solid-State Fluoride-Ion Batteries

Abstract: All-solid-state fluoride-ion batteries (FIBs) are regarded as attractive alternatives to traditional energy storage systems because of their high energy density; however, they are not applicable at room temperature owing to sluggish ion transport in both the electrolyte and electrode. In this study, a rational design of a Cu–Pb nanocomposite is reported, which was tested as a room-temperature cathode material for all-solid-state FIBs. Following electrochemical pretreatment, self-generated PbF2 could act as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…As reported previously, 7–26 the rechargeable Q values for liquid-electrolyte-type FIBs are somewhat lower than those for all-solid-state FIBs. In this study, Q cha at the first cycle was only ∼9 mA h g −1 when the discharge cut-off voltage was set to 0.1 V [Fig.…”
Section: Resultssupporting
confidence: 73%
“…As reported previously, 7–26 the rechargeable Q values for liquid-electrolyte-type FIBs are somewhat lower than those for all-solid-state FIBs. In this study, Q cha at the first cycle was only ∼9 mA h g −1 when the discharge cut-off voltage was set to 0.1 V [Fig.…”
Section: Resultssupporting
confidence: 73%
“…Sr 2 MnO 3 F 2 gave a capacity of 84 mAh g –1 with plateaus at 0.2 and −0.2 V during the discharging process and a capacity of 83 mAh g –1 with plateaus at −0.2 and 0.3 V during the charging process (Figure b). Although the cyclability of Sr 2 MnO 3 F 2 was worse than that of LaSrMnO 4 F (Supporting Figure 4b), it was significantly better than those of the conversion-type electrodes. ,,, Comparing the capacity retention at various current densities of LaSrMnO 4 F and Sr 2 MnO 3 F 2 , Sr 2 MnO 3 F 2 showed better capacity retention at high current densities to LaSrMnO 4 F (Figure c).…”
Section: Resultsmentioning
confidence: 94%
“…Although the cyclability of Sr 2 MnO 3 F 2 was worse than that of LaSrMnO 4 F (Supporting Figure 4b), it was significantly better than those of the conversion-type electrodes. 1,9,32,33 Comparing the capacity retention at various current densities of LaSrMnO 4 F and Sr 2 MnO 3 F 2 , Sr 2 MnO 3 F 2 showed better capacity retention at high current densities to LaSrMnO 4 F (Figure 2c).…”
Section: ■ Introductionmentioning
confidence: 95%
“…Several recent studies on all-solid-state FIBs have demonstrated improved performance in Cu cathodes by tailoring electrode chemistry (using a copper-gold alloy, Cu 3 Au) and electrode composition (via formation of a Cu/PbF 2 composite). 47,48 In both cases improved capacity retention was demonstrated up to 20 cycles. The addition of ionically conductive PbF 2 further enabled cycling at the full theoretically capacity at room temperature.…”
Section: Selection Of Electrode Materialsmentioning
confidence: 88%